(3GdeUaj eNJUQ GdeSJUaj aj GdNdGas - (3YHO Gddg Hf CMeO Hf eMehO GdfSaj, CHh GdHQcGJ, MGaX GdOjf,J (B710 (3g` s ((3EHQGgje Hf HfOGQ EHQGgje GdYQGbi s)
(3ChdgG (B:s
(3GdMeO def JeJ fYeJg hGdTcQ def SHbJ QMeJg bhdg HGSe GdEdg QH cd YHO hGdMeO ddg hdi GdMeO s
(3BNQgG (B:s
(3hdfNJe GdcJGH HGdOYGA GdeCKhQ Yf GdfHi Udi Gddg Ydjg hSde (B: (3Gddge Efi CSGdc GdKHGJ ai GdCeQ hGSJZaQc deG JYde Efc CfJ YdGe GdZjhH s
(3GdfSNI HgG MhGTs
(3ai GdeDda ef JCdja cJGHg SfI (B670s
(3hgPG GdeUai TQM defXheI CHh MaU GdfSai ai GdNdGa s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs